2014
DOI: 10.1042/bst20140078
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular redistribution of acetyl-CoA, the pivotal point in differential susceptibility of cholinergic neurons and glial cells to neurodegenerative signals

Abstract: Intramitochondrial decarboxylation of glucose-derived pyruvate by PDHC (pyruvate dehydrogenase complex) is a principal source of acetyl-CoA, for mitochondrial energy production and cytoplasmic synthetic pathways in all types of brain cells. The inhibition of PDHC, ACO (aconitase) and KDHC (ketoglutarate dehydrogenase complex) activities by neurodegenerative signals such as aluminium, zinc, amyloid β-peptide, excess nitric oxide (NO) or thiamine pyrophosphate deficits resulted in much deeper losses of viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…(1) As a matter of fact, biosynthesis of ACh is directly linked to mitochondrial glycolysis and citric acid cycle. In mitochondria, glucose converted to pyruvate, and thereby production of acetyl-Coenzyme A ( A-CoA ) [41], (2) which is partly used in the citric acid cycle for generation of bioenergetic molecules such as ATP, and (3) the rest may enter into the cytoplasm for instance for biosynthesis of ACh by ChAT, which is apparently required for activation of the mitochondrial nAChR ( mt- nAChR). (4) The mt-nAChRs and their regular activation by intracellular ACh may hence function as a biodynamic sensor.…”
Section: Discussionmentioning
confidence: 99%
“…(1) As a matter of fact, biosynthesis of ACh is directly linked to mitochondrial glycolysis and citric acid cycle. In mitochondria, glucose converted to pyruvate, and thereby production of acetyl-Coenzyme A ( A-CoA ) [41], (2) which is partly used in the citric acid cycle for generation of bioenergetic molecules such as ATP, and (3) the rest may enter into the cytoplasm for instance for biosynthesis of ACh by ChAT, which is apparently required for activation of the mitochondrial nAChR ( mt- nAChR). (4) The mt-nAChRs and their regular activation by intracellular ACh may hence function as a biodynamic sensor.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of these diseases are complex and still remain unknown, due to both genetic and sporadic issues. Neuropathological and radiological studies have shown that these diseases are accompanied by serious inflammation, during which the glial response may be a significant issue in the occurrence of neurons losses [42, 43]. Studies based on molecular biology show that the causes of neurodegenerative disorders are multi-systemic in vivo, and may be affected by a cascade of multiple signaling pathways [44].…”
Section: Astrocytes Morphology and Functions In The Cnsmentioning
confidence: 99%
“…Mature neurons prefer mitochondrial energy metabolism instead of glycolysis [ 37 ]. This metabolic shift (tracked by pyruvate dehydrogenase (PDH) activity, acetyl-CoA and pyruvate levels) was clearly observed in primary neurons treated by either NGF or db-cAMP ( Table 3 , Figure 4 A,C).…”
Section: Resultsmentioning
confidence: 99%
“…To study cAMP—dependent protein kinase A activation using the in vivo model, we considered daily acute theophylline challenge instead of db-cAMP treatment. Theophylline injection has been proven to have a spread effect across the entire animal body (including the brain), while db-cAMP might not reach brain tissue, unless microinjected into the particular brain region [ 37 ].…”
Section: Resultsmentioning
confidence: 99%